2012
DOI: 10.1111/j.1743-6109.2012.02847.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phenylephrine on Spontaneous Activity and L-Type Ca2+ Current in Isolated Corpus Cavernosum Myocytes

Abstract: Introduction Norepinephrine is important in maintaining detumescent tone in the corpus cavernosum, although the mechanism is incompletely understood. As α-adrenoceptor-induced tone is antagonized by L-type Ca2+ channel blockers, it is usually assumed that direct modulation of this current is involved. However, the effects of α-adrenoceptor agonists have never been directly examined on L-type current in corpus cavernosum myocytes (CCSMC), leaving open other possibilities. In particular, CCSMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…In the present study, we have provided the first functional evidence that ATP induces an inward cationic current in corpus cavernosum myocytes. Ion substitution experiments showed that this is distinct from the inward current mediated by I ClCa and therefore different from the spontaneous inward currents generated by these cells [17,18] and from the previously reported inward currents generated by phenylephrine [19]. As P2X receptors are known to be ligand‐gated cation channels [6], it was highly likely that the cation current described here was mediated by P2X receptors.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…In the present study, we have provided the first functional evidence that ATP induces an inward cationic current in corpus cavernosum myocytes. Ion substitution experiments showed that this is distinct from the inward current mediated by I ClCa and therefore different from the spontaneous inward currents generated by these cells [17,18] and from the previously reported inward currents generated by phenylephrine [19]. As P2X receptors are known to be ligand‐gated cation channels [6], it was highly likely that the cation current described here was mediated by P2X receptors.…”
Section: Discussioncontrasting
confidence: 57%
“…When isolated corpus cavernosum smooth cells were held under voltage clamp at −60 mV, they often exhibited spontaneous Ca 2+ ‐activated Cl − currents (I ClCa , Figure A–C) as described previously [18,19]. In 84% of cells, a 20‐second application of ATP (20 μM) evoked a single transient inward current that decayed despite the continued presence of ATP (Figure A).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations